Effect of microwave sintering on the mechanical and structural properties of pewter alloy - Mohamed Ariff, Tasnim Firdaus; Gabbitas, Brian (ooi Senior Academy, 2008)
97%Sn 2%Cu 1%Sb (pewter) alloys were examined to determine the effect of green density, sintering time and sintering temperature on the mechanical and structural properties of the conventional and microwave sintered compacts. Two compaction loads; 30kN and 40kN were used to produce the samples with different green densities. Eight different time-temperature combinations were used for each heat treatment. Samples with a higher green density resulted in a higher sintered density and higher hardness. Longer sintering time and higher sintering temperatures resulted in higher densities, larger grain size and higher hardness for both sintering methods. However, the microwave sintered samples in general have finer microstructures, higher densities and higher hardness compared to the conventional sintered samples in a much shorter duration. Better mechanical and structural properties were achieved by microwave sintering in 15 minutes compared to 120 minutes by conventional sintering.